INSULIN DEFICIENCY AMONG NEWLY DIAGNOSED TYPE 2 DIABETICS - Naseem, Tahira; Yasmin, Riffat; Afzal, Naeema; Farrukh, Ambreen; Paul, Rubina Faisal; Hassan, Mukhtiar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Any patient above the age of 40 years, coming with the symptoms of diabetes is labelled as type 2 diabetic. If insulin levels are included in the protocol for initial investigations of diabetic patients, they can be differentiated as having insulin deficiency or insulin resistance. They can thus be treated accordingly. This study was conducted to see the prevalence of insulin resistance and insulin deficiency in newly diagnosed type 2 diabetics. Methods: This study was conducted on 75 newly diagnosed diabetic subjects, and 75 control subjects for comparison. Fasting serum insulin was assayed by ELISA and HOMA-IR index was calculated. The diabetic subjects with fasting hyperglycaemia and serum insulin level below 20 µIU/ml and HOMA-IR index below 3.5 were grouped as insulin deficient (Group-A), and the diabetic subjects with fasting insulin level above 20 µIU/ml and HOMA-IR index above 3.5 were grouped as insulin resistant (Group-B). Results: Twenty-eight percent subjects were found to have insulin level below 20 µIU/ml while 72% subjects had insulin resistance. When gender was taken into consideration, it was seen that 18.7% males had fasting insulin level of 6.98±0.737 µIU/ml and 9.3% females had fasting insulin level of 5.21±0.885 µIU/ml while 32% males and 40% females had insulin resistance. The mean age of male subjects with insulin resistance was significantly higher compared to the male subjects with insulin deficiency. Mean weight and body mass index of the male and female subjects having insulin resistance was significantly higher than their respective control groups and also higher than the subjects with insulin deficiency. Pearson coefficient of correlation was calculated for fasting serum insulin level with age and BMI. A significant positive correlation was observed between fasting serum insulin and age of females with insulin resistance. Conclusion: A considerable number of persons who develop diabetes after 40 years of age but are not insulin resistant. Twenty-eight percent subjects have relative insulin deficiency, and 72% subjects have insulin resistance. Keywords: Type 2 diabetics, insulin deficiency, BMI